Incidence of COVID-19 Vaccination-Related Uveitis and Effects of Booster Dose in a Tertiary Uveitis Referral Center - Chew, Milton C.; Wiryasaputra, Shaan; Wu, Meihui; Khor, Wei Boon; Chan, Anita S. Y. (Frontiers in Medicine, 2022)
Background We report vaccine and booster-related uveitis in Singapore, a country with high vaccination and booster rates to highlight the differences and potential role of prophylactic treatment for sight-threatening infectious uveitis. Methods Clinical data extracted from the de-identified uveitis database in Singapore National Eye Center. Six patients (eight eyes) developed uveitis within 14 days after undergoing COVID-19 vaccination (primary and/or booster). Results All patients received two doses of COVID-19 vaccination, and 1.39% (6/431) developed COVID-19 vaccine-related uveitis. Fifty-percent% (3/6) with non-infectious anterior uveitis (NIAU) presented with a non-granulomatous anterior uveitis (AU). The remaining (3/6) presenting with a granulomatous AU were diagnosed with reactivation of cytomegalovirus, varicella-zoster virus and toxoplasma chorioretinitis, respectively. All the patients responded to definitive treatment specific to their diagnosis. The mean visual acuity at presentation was 0.36 ± 0.20 logMAR and improved to 0.75 ± 0.09 (p = 0.009). Mean time from vaccination to uveitis was 9.7 (range: 3–14) days. All patients developed uveitis after second vaccination dose. 16.67% (1/6) patients had a recurrence after the third booster dose. None of the three patients with infectious uveitis developed recurrence but had received maintenance therapy up to or during the booster. Conclusion Uveitis after COVID-19 vaccination is uncommon. In our series, a higher rate of reactivations of latent infections was seen. With definitive treatment, all cases were self-limited without systemic sequelae. Prophylactic treatment during booster vaccine may prevent reactivation of sight-threatening infections and reduce morbidity although risk-benefits should be considered for individual patients given the low rate of occurrence.